A submarine morphotectonic analysis combining GIS-based methods and virtual reality: Case study of the low-rate active thrust faulting off Boumerdès (Algeria) - Déverchère, Jacques; Barbé, Antoine; Kernec, Maxime; Jaud, Marion; Ruault, Riwalenn (Frontiers in Earth Science, 2022)
The Algerian margin is located at the slow-rate convergent boundary between African and Eurasian plates and experienced several strong earthquakes in the last centuries. Among them, the 2003 Mw 6.8 Boumerdès event has triggered large turbidity currents in the slightly concave canyons of the slope and numerous cable breaks in the abyssal plain. In this study, we explore where, how and when the tectonic inversion of the margin off Boumerdès has left witnesses in the seafloor morphology and whether the observed deformation correlates with the 2003 coseismic rupture zone and with the Plio-Quaternary sedimentation. We have performed a careful analysis of the seafloor morphology and subsurface seismic reflectors at the landscape scale and along/between canyons by combining classical GIS-based methods and Virtual Reality techniques. From the mid-slope to the deep basin off the ∼60 km long Boumerdès-Dellys coast, we evidence large knickpoints corresponding to the development of four main cumulative fault scarps and two perched basins which are deeply incised by steep canyons and gullies. We interpret these structures to result from frontal propagation of two main south-dipping thrusts by upper crustal décollement ramping, evidencing an incipient sub-thrust imbrication in a stage of initiation of an accretionary wedge. The flat-ramp thrust geometry and their along-strike segmentation explain the development and shape of the perched basins in the backlimb of fault-related folds. The onset of growth strata is dated at 1.5 ± .5 Ma on the slope and .9 ± .3 Ma in the deep basin. The length, position, strike and segmentation of the older, southern thrust ramp are consistent with the coseismic characteristics of the Mw 6.8 2003 earthquake. The cumulative vertical scarp throw exceeds 1 km, supporting Quaternary shortening rates of 1.6 ± .7 mm/yr, in agreement with geodetic strain rates across the western Mediterranean basin. Virtual Reality offers powerful and promising means to correlate seismic imagery and seafloor morphology and is of great help to improve the robustness of tectonostratigraphic interpretation.